THE EFFECTIVENESS OF THE IMPLEMENTATION OF PRESIDENTIAL INSTRUCTION (INPRES) NO. 5/2019 IN ERADICATING THE PEATLAND FIRES IN THE KALIMANTAN REGION - Syahrir Roni Geyasra; Renate Septiana Widiaputri; Sathya Reysha Wacanno (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
The forest and peat permit moratorium is a policy aimed at improving and perfecting the ongoing management of forests and peatlands. The policy also aims to continue efforts to reduce emissions from deforestation and forest degradation. This moratorium policy for forest and peat permits was created during the reign of former President Susilo Bambang Yudhoyono in 2011 and is extended every two years. In 2019, the policy was ordered as permanent moratorium by President Joko Widodo and formulated in Presidential Instruction No. 5/2019. Since the implementation of the moratorium, there has been a decrease in the rate of deforestation of forests and peatlands in Indonesia. However, forest and land fires still occur, especially in the Kalimantan region. Even in 2019, significant forest and peatland fires have occurred in Kalimantan since a similar incident in 2015. The hotspots of these fires are scattered in various provinces in Kalimantan, disrupting public health due to the thick smoke generated. This study is analyzed using the Theory of Policy Implementation by George C. Edward III. Through policy research, this research is examined qualitatively to analyze the effectiveness of the implementation of Presidential Instruction No. 5/2019 on the phenomenon of peatland fires in the Kalimantan region. The results of this study indicate that there are still weaknesses in implementing Presidential Instruction No. 5/2019 so that it is said to be less effective in eradicating forest and peatland governance. Keywords: Effectiveness, Policy Implementation, Presidential Instruction, Peatland Fires